EFFECTS OF COVID-19 PANDEMIC ON THE CAREERS OF FREELANCE DANCE INSTRUCTORS AND QUALITY OF LIFE - Singkha , Pongpop; Supaporn , Salee (Journal of Faculty of Physical Education, 2024)
The purpose of this study was to determine the effects of the COVID-19 pandemic on the careers of freelance dance instructors and their quality of life. The participants consisted of 20 freelance dance instructors, 16 males and 4 females, in the Bangkok metropolitan area. The data were collected through interview, critical incidence and stimulated recall with photos. The findings indicated three themes on the impact of the COVID-19 pandemic on freelance dancers. First, the impact included five categories, as follows: (1) reduction of dance classes and participants per session (2) enforcing instructors to conduct online dance classes; (3) exhaustion and breathing difficulty with masks; (4) hurting and irritating nostrils because of too many ATK tests; and (5) increasing expense. Second, income during the COVID-19 pandemic decreased by 50.86%. Third, self-evaluation mean score on quality of life, from 1-9, lower scores indicated a lower impact than those higher scores, was 6.50, implying the great impact of the COVID-19 pandemic, particularly the physical, mental, social relationship and environmental domains. In summary, the COVID-19 pandemic had a negative impact on the career of freelance dance instructors, hindered their work, and decreased both their income and quality of life.